Literature and Militant Testimony in the Tupakatari Bolivian Guerrilla: Raquel Gutiérrez and the Scientific Discourse as Autobiographical Narrative of a "Professional Revolutionary" (Palimpsesto, 2019)
The present work analyzes the autobiographical book ¡To mess up! For an open history of the social struggle, by Raquel Gutiérrez, militant and founder of the Tupac Katari Guerrilla Army of Bolivia. In the perspective of the History of the Recent Past, one inquires into the political nature of Rachel's memory, in the construction of her story, as well as in the contexts of enunciation and reception of her work. The hypothesis is that the authorchooses as the "truth effect" for herautobiographical narrative, the scientific discourse, the most credible of the enunciation locus, to elaborate a critical theoretical analysis of the revolutionary militancy and its armed apparatuses. However, in its narrative strategy the traumatic imprint of the trauma is notorious, since the author is permanently hiding from her own autobiography, omitting intimacy, subjectivity and those aspects of the body and properly human that are always present in every militant.
Keywords: Testimonial literature; Raquel Gutiérrez; Bolivian guerrilla; Armed Tupakatarism; EGTK